Profil Gizi Buruk pada Balita di Kabupaten Lombok Utara - Hafizah Hafizah; Pariawan Lutfi Ghazali (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2010)
According to data in 2005, number of malnutrition's under 5th years children cases in NTB reach 10% from all of under 5th year children on the average 498.000 people. Amount number of malnutrition's under 5th year children can be caused of social-economy status, parent's education and knowledge about nutrition, child rearing patterns and accompanying disease. Malnutrition profile of under 5th year children is very important to know the life of malnutrition under 5th year children that seen from nutrition status, age, clinical symptom, social-economy and accompanying disease, also to know what makes it easier malnutrition and what therapy that must given to malnutntion patient. Knowing malnutrition profile in under 5th year children in North Lombok NTB in 2008 and 2009. This study is was done of subject's medical report and observation, that is under 5th year children that have malnutrition in 2008 and 2009 using z score by weight/height. This study's structured form that includes the information required in the research, that is structured form that contains required info, like identity (name, age, sex, address source of funds), accompanying diseases, clinical symptom. The data obtained were performed using Excel program, then result from that frequency distribution was shown in table and diagram. The study results that amount of malnutrition patients reach 59 patients (97%) from 59 one, the highest age who suffer from malnutrition 18-24 month (20%), accompanying diseases suffered by most of diarrhea (25%), most climcal symptom are thin (39%), he source of funds used by many is not known that is as much 52%, and patient who received additional therapy as much as that 68%. Conclusions from this study, amount number of malnutrition's under 5th year children with 18- 24 month of age that accompanied by concomitant diseases in North Lombok in 2008 and 2009 was caused by low social-economy and less parent's education and knowled#e about nutrition.